Titoaffect - tracing objects and memories of socialism in post-socialist Croatia - Škrbić Alempijević, Nevena (Array, 2014)
Titoaffect – tracing objects and memories of socialism in post-socialist Croatia This paper deals with memories of socialism and the affective power of socialist material culture in the aftermath of memory cleansing in post-socialist Croatia. Objects that we analyze are associated with the image of Josip Broz Tito, a life-long ex-Yugoslav president, materializations of whom have a potential to affect people more than thirty years after his death. Pondering upon motifs that previously had been celebrated and mythologized, and ended to be concealed, exposed to silence and reserved to the private sphere during the 1990s, we aim to show that the materiality of socialism continues its afterlife by triggering extraordinary affects. We argue that, in the context in which socialism is exposed to social forgetting, these objects tempt reflexive, individual and private acts of remembering. In comparison to the concept of Titostalgia, related to the sunny side of memory (Velikonja 2008), Titoaffect encompasses a whole span of differently charged reactions to objects bearing the image of Tito. By this term we address a variety of emotional, bodily and intellectual responses, sensory experiences, narrative expressions and social practices. In our research we focus on different modes of contact with the materiality of socialism and point to the affective dynamics related to Tito. We will present three case studies and accompanying types of Titoaffect. In the first case study the appearance of Tito’s picture unexpectedly “trashes” a birthday party, providing us with an insight in the affects of indignation, shock and repugnance. In the second case study we observe how the Tito lettering, shaped by rosebushes in a public park, is enveloped in introspective silence and clandestineness by tenants of nearby buildings. The third case study casts light on flea markets where people trade images of Tito and exchange mostly positively connoted memories of one’s own pasts.